PROMOTING EFFECTIVE ENGLISH LANGUAGE TEACHING PRACTICES FOR HOTEL STAFF: A PRELIMINARY STUDY - Nurdiana , Nurdiana (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The hotel, hospitality, and tourism industries have rapidly developed over the past few years. English skills are undoubtedly required in these industries, especially for those who work in five-star and international hotels, including the ones located in Indonesia. It turns out, however, that many hotel staff seem to have a lack of appropriate English language use competence in their workplace. Having taught English to hotel staff for almost two years, it revealed that only a few of them can communicate in English appropriately. Some of the staff do not even know how to make sentences in English. Taking this phenomenon into account, effective English language teaching practices are urgently needed and therefore, this study attempts to discuss some strategies to promote effective English language teaching practices for hotel staff. The strategies were investigated by interviewing the hotel staff who attended an English class held by a five-star hotel located in South Jakarta, Indonesia. The interview consisted of open questions which resulted in significant data on what makes most of the hotel staff unable to communicate in English appropriately, how the teacher should teach the hotel staff, and lastly, what should be discussed and learned during the teaching and learning sessions. Keywords: English, hotel staff, teaching strategies